Strategy to Strengthen the Sakinah Family through Fiqh Education on Gender Equality for Students of the Islamic Science University Malaysia (USIM): Strategi Penguatan Keluarga Sakinah melalui Edukasi Fiqih Kesetaraan Gender bagi Mahasiswa University Sains Islam Malaysia (USIM) - Asfiyak, Khoirul; Jannah, Shofiatul; Muslim, Moh; Ayuni Lestari, Niken (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Students of the Faculty of Syariah and Law at Universiti Sains Islam Malaysia (USIM) hold a strategic position as pioneers of social change in various aspects of life. Social issues that advocate for justice, welfare, and equal rights present significant challenges for these students. This is particularly true in matters of gender equality and justice, which have become widely discussed topics over the past two decades across all sectors. Indeed, social justice and quality of life stem from a prosperous family, known as a sakinah family. Through mentoring and education on gender equality fiqh, USIM students are encouraged to have the same platform, knowledge, and experience in responding to various social inequalities caused by gender-biased values. Based on data analysis, there has been a significant change among USIM students, who initially doubted the importance of gender equality approaches in resolving various family issues, becoming more open and determined to plan actions to introduce the concept of a sakinah family based on gender equality fiqh within their families and communities.